EVALUATING TEAM-BASED ELECTRONIC PORTFOLIO ASSESSMENT - Zainal Abidin, Azizan (2009)
The implementation of the traditional assessment method in the teaching and learning of mathematics at Universiti Teknologi PETRONAS is by far the most common practice. It is perhaps the quickest way of measuring students’ learning, cognitively. However, in learning, measuring affective and psychomotor skills are as important. This paper intends to discuss some preliminary findings obtained when the author integrates the electronic portfolio as an alternative assessment method in the teaching and learning of Differential Equations. One hundred and ninety undergraduates in their first semester enrolled in Petroleum Geoscience, Chemical and Petroleum Engineering Programs are involved in the study. Participants work in teams of five, guided by written and verbal instructions and criterion-based scoring rubrics. Within a timeframe of seven weeks, each group submits their work saved on a compact disc as an assignment considered an integral part of their coursework. The author uses a criterion-based scoring rubric to evaluate each electronic portfolio, employs peer assessment for moderation of the ePortfolio evaluation process and uses a questionnaire to discover participants’ responses towards the integration of the electronic portfolio as an assessment method. The results provide some intuition of students’ attitude towards such an alternative assessment approach.